2011
DOI: 10.1007/s11604-011-0595-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with upstaging of ductal carcinoma in situ diagnosed by core needle biopsy using imaging guidance

Abstract: High-grade DCIS, using a smaller needle, and the presence of comedonecrosis in the CNB specimen were associated with a higher risk for invasive carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The relatively low negative predictive value seen in our results 62% compared to previously reported values 90-98.9% (23)(24)(25)(26) resulted from the 8.4% false negative rate and underestimation of high-risk lesions. Several factors can contribute to this low NPV: 1) The nature of the lesion: histological underestimation occurs when the CNB samples high risk areas with atypical ductal hyperplasia or intraductal lesion while the rest of the lesion contains invasive carcinoma (9,27,28). ADH is a risk factor for cancer and can also be found alongside invasive cancer (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively low negative predictive value seen in our results 62% compared to previously reported values 90-98.9% (23)(24)(25)(26) resulted from the 8.4% false negative rate and underestimation of high-risk lesions. Several factors can contribute to this low NPV: 1) The nature of the lesion: histological underestimation occurs when the CNB samples high risk areas with atypical ductal hyperplasia or intraductal lesion while the rest of the lesion contains invasive carcinoma (9,27,28). ADH is a risk factor for cancer and can also be found alongside invasive cancer (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors can contribute to this low NPV: 1) The nature of the lesion: histological underestimation occurs when the CNB samples high risk areas with atypical ductal hyperplasia or intraductal lesion while the rest of the lesion contains invasive carcinoma (9,27,28). ADH is a risk factor for cancer and can also be found alongside invasive cancer (27)(28)(29). Underestimation of ADH is one of the major issues in US guided CNB which could range from 0-100% (30).…”
Section: Discussionmentioning
confidence: 99%
“…Our model can help surgeons decide whether SLNB should be performed. Previous research has focused on exploring relevant clinical predictors (3,9,10,17,18). Multiple studies have reported clinical predictors for upstaging after CNB, such as age, size of the mass, and higher nuclear grade, and the relevant prediction models were established based on these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Distinction between DCIS and invasive carcinoma before surgery has been addressed previously. Recently, research has focused on corresponding clinical factors as predictors of postoperative upstaging of pure DCIS diagnosed preoperatively by CNB (3,9,10). However, the evaluation of some of these clinical factors have been subjective, and the factors are difficult to apply in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Nondiagnostic samples, typically classified as those which are void of epithelial cells (4), occur in up to 35% of palpation-guided FNAB (1-3) procedures and 12% of image-guided CNB procedures targeting nonpalpable lesions (9). These difficulties lead to rebiopsy in approximately 4% of the patients that undergo percutaneous procedures (10-11). …”
Section: Introductionmentioning
confidence: 99%